Effects of heterogeneous aging in compressed HNBR and EPDM O-ring seals. (April 2016) - Kömmling, Anja; Jaunich, Matthias; Wolff, Dietmar
Abstract: Seals used in containers for dangerous goods need to maintain leak tightness for several decades. For investigating the change in seal material properties during aging, a comprehensive aging program on both uncompressed and compressed EPDM and HNBR seals was started. In order to obtain results closely related to practical conditions, O-rings with a full-scale cord diameter of 10 mm were aged. However, this set-up can lead to heterogeneous aging caused by diffusion-limited oxidation (DLO) effects. These effects depend on material, dimensions, time and temperature. Heterogeneous aging results in distorted bulk properties such as compression stress relaxation and compression set (CS) suggesting that HNBR has better performance than EPDM at 150 °C but which is not the case at 100 °C. The presence of heterogeneous material properties was shown by hardness measurements across the seal cross-section. If DLO-affected data is excluded, extrapolations of CS data are possible using time–temperature shifts and Arrhenius graphs. Exemplary CS values of 50% and 80% would be reached after approx. 10 years and 29 years, respectively for HNBR and after approx. 400 years and 1100 years, respectively for EPDM.